Shifts in the distribution of ixodid ticks parasitising cattle in Zimbabwe - Sungirai, Marvelous; Abatih, Emmanuel Nji; Moyo, Doreen Zandile; De Clercq, Patrick; Madder, Maxime (Wiley (The Royal Entomological Society), 2018)
Ixodidae) in Zimbabwe, a cross‐sectional survey was carried out between September 2013 and May 2015 at 322 dip tanks. A total of 15 tick species were collected, namely: Amblyomma hebraeum Koch (65.2%, n = 210/322), Amblyomma variegatum Fabricius (14.9%, n = 48/322), Hyalomma rufipes Koch (62.4%, n = 201/322), Hyalomma truncatum Koch (37.9%, n = 122/322), Rhipicephalus appendiculatus Neumann (60.6%, n = 195/322), Rhipicephalus compositus Neumann (0.3%, n = 1/322,), Rhipicephalus decoloratus Koch (61.8%, n = 199/322), Rhipicephalus evertsi evertsi Neumann (65.2%, n = 210/322), Rhipicephalus lunulatus Neumann (4%, n = 13/322), Rhipicephalus microplus Canestrini (32%, n = 103/322), Rhipicephalus near punctatus Walker and Horak (7.1%, n = 23/322), Rhipicephalus simus Koch (5.6%, n = 18/322) and Rhipicephalus cf. turanicus Pomerantsev (3.4%, n = 11/322). Compared with previous surveys, changes in the distribution of A. hebraeum, A. variegatum and R. microplus were recorded. The distributions of other tick species have largely remained unchanged. Factors which might have influenced these changes and the possible impacts on the epidemiology of tick‐borne diseases are discussed.